2016
DOI: 10.3390/ma9070518
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-Sintered Zirconia Surface Conditioning on Shear Bond Strength to Resin Cement

Abstract: This study analyzed the shear bond strength (SBS) of resin composite on zirconia surface to which a specific conditioner was applied before sintering. After sintering of either conditioner-coated or uncoated specimens, both groups were divided into three subgroups by their respective surface modifications (n = 10 per group): no further treatment; etched with hydrofluoric acid; and sandblasted with 50 µm Al 2 O 3 particles. Surfaces were characterized by measuring different surface roughness parameters (e.g., R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
11
1
1
Order By: Relevance
“…Pretreatment of zirconia oxide-based ceramic must be performed but must not compromise the long-term restoration longevity. Creating microretentions in a highly resistant ceramic substrate with a view to preparing it for cementation is not an easy task, because its surface is compact, hard and difficult to change ( 9 , 21 ). Additional studies should be performed to determine the efficacy of the surface treatment methods for zirconia oxide-based ceramics, particularly with the use of stronger acids.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of zirconia oxide-based ceramic must be performed but must not compromise the long-term restoration longevity. Creating microretentions in a highly resistant ceramic substrate with a view to preparing it for cementation is not an easy task, because its surface is compact, hard and difficult to change ( 9 , 21 ). Additional studies should be performed to determine the efficacy of the surface treatment methods for zirconia oxide-based ceramics, particularly with the use of stronger acids.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the ABPA procedure, many studies in the literature described the elimination of abraded zirconia particles before proceeding with cementation. This might be performed by rinsing the samples with water or air/water spray [40,41] or through an ultrasonic bath containing distilled water or ethanol [22,41,42]. On the contrary, no rinsing of air-borne particle abraded zirconia was described by authors, taking into account a risk of alteration of the freshly air-abraded surface with a reduction of the bonding efficacy, despite other studies clearly showing that the cleaning method has little or no effect [43].…”
Section: Discussionmentioning
confidence: 99%
“…The bonding of ceramic restorations commonly involves acid etching and/or sandblasting procedures [32,33]. In the previous studies, it was reported that the shear bond strength of pre-sintered zirconia and the veneering porcelain did not change by conditioner treatment, but the failure mode was improved after thermal cycling [32].…”
Section: Discussionmentioning
confidence: 99%
“…The bonding of ceramic restorations commonly involves acid etching and/or sandblasting procedures [32,33]. In the previous studies, it was reported that the shear bond strength of pre-sintered zirconia and the veneering porcelain did not change by conditioner treatment, but the failure mode was improved after thermal cycling [32]. It was also identified that the sandblasted zirconia surfaces had significantly higher shear bond strengths than non-treated and chemically etched surfaces without thermocycling, irrespective of conditioner treatment, and the highest shear bond strength and improved failure mode was confirmed by the application of both conditioner treatment and sandblasting [33].…”
Section: Discussionmentioning
confidence: 99%